Analisis Pembangunan Perdamaian Dan Rekonsiliasi Paska Konflik Sunni Dan Syiah Di Sampang, Madura (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2021)
In a pluralistic society, social conflict often occurs with uncanny complexity. The Sampang conflict between the Sunni and Shia Muslim communities has an impact on several things such as instability, social uncertainty, also the decadence of unity and integrity. This article wants to analyze the background of the conflict. In addition, this essay also attempts to explain the post-conflict peace building and reconciliation process and its important elements. This kind of conflict requires a special approach so that similar conflicts do not recur in the future. The method used in this research is qualitative and descriptive analysis method. This research found that the conflict happened because of the difference perception of each groups regarding the history of Islam which affected stereortye between Sunni as majority group to Shia as Minority group in Sampang, Madura. This research also found that the government of Indonesia both local and Jakarta, failed to facilitate peace building and reconciliation process. It can be shown when the Shia refugees are rejected to come back to their village in Sampang by the Sunni Majority.
Keywords: Conflict; Sampang; Madura; Sunni; Syiah; peace building; reconciliation